The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3390/ijerph17124345
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and Smoking in the Home: Parents’ Accounts of Using Nicotine Replacement Therapy to Protect Their Children from Second-Hand Smoke

Abstract: Evidence and campaigns highlighting smoking and second-hand smoke risks have significantly reduced smoking prevalence and denormalised smoking in the home in Scotland. However, smoking prevalence remains disproportionally high in socioeconomically disadvantaged groups. Using stigma as a theoretical lens, this article presents a thematic analysis of parents’ accounts of attempting to abstain from smoking at home, using nicotine replacement therapy (NRT), in disadvantaged areas of Edinburgh and the Lothians. Smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 66 publications
0
6
0
2
Order By: Relevance
“…Silván-Ferrero et al [ 28 ] proposed a mediational path analysis and found that the association between higher levels of self-stigma and lower levels of quality of life among the participants with physical disability was mediated via resilience. Lewis et al [ 29 ] utilized a qualitative design to understand the self-stigma of smoking among parents who had child(ren) at home in Scotland. Through thematic analysis, Lewis et al [ 29 ] observed that parents may be afraid of disclosing their smoking habits in their societies because of their smoking self-stigma.…”
Section: Findings Of the Contributions In The Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Silván-Ferrero et al [ 28 ] proposed a mediational path analysis and found that the association between higher levels of self-stigma and lower levels of quality of life among the participants with physical disability was mediated via resilience. Lewis et al [ 29 ] utilized a qualitative design to understand the self-stigma of smoking among parents who had child(ren) at home in Scotland. Through thematic analysis, Lewis et al [ 29 ] observed that parents may be afraid of disclosing their smoking habits in their societies because of their smoking self-stigma.…”
Section: Findings Of the Contributions In The Special Issuementioning
confidence: 99%
“…Lewis et al [ 29 ] utilized a qualitative design to understand the self-stigma of smoking among parents who had child(ren) at home in Scotland. Through thematic analysis, Lewis et al [ 29 ] observed that parents may be afraid of disclosing their smoking habits in their societies because of their smoking self-stigma. Therefore, parents may perform hidden smoking and are not confident enough to stop smoking.…”
Section: Findings Of the Contributions In The Special Issuementioning
confidence: 99%
“…Poor existing relationships between participants and pharmacy staff also served as a barrier, as was the case for two participants, who were distant relatives, who reported having negative interactions with pharmacy staff in the past ( Figure 3 , quote 4). These findings are presented and discussed elsewhere [ 30 ]. However, in most cases, participants reported more positive, supportive interactions with pharmacy staff.…”
Section: Resultsmentioning
confidence: 72%
“…In Scotland, there are over twice as many pharmacies in the most deprived areas as in the least deprived areas [ 32 ], and they also deliver smoking cessation services so would be well placed to support parents. Supportive encouragement in non-judgemental environments is key to support parents to create a smoke-free home without perpetuating stigma [ 30 ]. To our knowledge, engaging community pharmacies more directly in providing NRT for temporary abstinence to create a smoke-free home has yet to be explored, and this approach warrants further research.…”
Section: Discussionmentioning
confidence: 99%
“…The role of a parent involves many obligations: parents must be responsible for their own health and the health of the offspring, provide for the child's needs and serve as an educational figure, as the parent is the most important socialising agent, whose job is to chart a right path for children (Lobato et al, 2017). For example, there is a well-known phenomenon of adults who change their status to that of parents and stop smoking (Lewis et al, 2020). There is even greater expectation that this changeover will take place, even more strongly, when it comes to illegal psychoactive substances, and certainly when it comes to addictive ones.…”
Section: Discussionmentioning
confidence: 99%